The Impact of Service Technology and Innovation on Customer Service: An Exploration of Chatbots, Virtual Assistants, and Artificial Intelligence - Luthra, Bharat (Digital Repository of Theses, 2026)
This dissertation examines the impact of service technology and innovation on customer service, focusing on the integration of chatbots, virtual assistants, and artificial intelligence (AI) in contemporary business environments. The study aims to explore how these technologies influence service efficiency, customer satisfaction, and organizational performance, while identifying the opportunities and challenges associated with their adoption. A mixed-methods research approach was employed, combining quantitative and qualitative analyses to provide a comprehensive understanding of AI-driven service transformation. Quantitative data were collected from customer service operations across multiple sectors, assessing metrics such as response time, resolution rate, cost efficiency, and satisfaction indices. Qualitative data were gathered through structured interviews and thematic analysis to capture user experiences, perceptions of trust, empathy, and usability of AI-enabled service tools. The Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT) frameworks guided the evaluation of user acceptance and behavioral intent toward these technologies. The results indicate that the deployment of chatbots and virtual assistants has substantially enhanced operational efficiency and service accessibility by automating repetitive processes and enabling round-the-clock support. Customers reported higher levels of convenience and responsiveness, contributing to improved satisfaction scores. However, findings also reveal notable constraints, including limited emotional intelligence, contextual comprehension gaps, and concerns regarding data privacy and ethical governance. These limitations underscore the need for balanced implementation strategies that preserve the human element within service interactions. The study concludes that the optimal customer service model is a hybrid configuration integrating AI technologies with human oversight to achieve both efficiency and empathy. This approach supports sustainable digital transformation while maintaining service quality and trust. The research contributes to academic and managerial discourse by providing empirical insights into how AI-driven innovation can be strategically leveraged to enhance customer experience, inform policy development, and strengthen organizational competitiveness in the evolving digital economy.